Study of production and the stability of styrallyl acetate nanocapsules using complex coacervation. (25th January 2016) - Xiao, Zuobing; Li, Wei; Zhu, Guangyong; Zhou, Rujun; Niu, Yunwei
Abstract: The styrallyl acetate (SA) nanocapsules were prepared using complex coacervation with gelatin (G) and gum arabic (GA) as the wall materials. The stability of the nanocapsules formed at different pH (4.8, 4.5, 4.2, 3.9, 3.6), wall concentration (0.5%, 1.0%, 1.5%, 2.0%, 2.5%) and the ratio of oil/emulsifier (1:2, 1:1, 2:1, 3:1) were evaluated. The results showed that the formation and stability of nanocapsules were influenced by these factors. The optimal process conditions were determined depending on the most stable aqueous system with the highest encapsulation efficiency. The optimum conditions were as follows: pH 4.5, the total concentration 1% and the ratio of core oil/emulsifier 1:1. The results of nuclear magnetic resonance (NMR) indicated that SA was encapsulated in G and GA successfully and the structure of SA and the wall materials was not changed. The further stability of optimal nanocapsules was assessed. Nanocapsules loaded with oil presented good stability over 8 months. Furthermore, the thermal stability was analysed by thermogravimetric analysis (TGA) and the results showed that the SA nanocapsules exhibited excellent thermal stability than the pure oil. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Nanocapsules‐loaded styrallyl acetate produced by complex coacervation improved the thermal stability of the core oil.